Pengaruh Sikap Kontrol Perilaku, dan Peran Fasilitator Pangan terhadap Pemenuhan CPPOB pada UMKM - Tengku Awalludin; Rulianda Wibowo; Fahmi Natigor (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to examine the effects of attitude, subjective norms, perceived behavioral control, and the role of facilitators in the Safe Food Goes to Campus (Pangan Aman Goes to Campus/PAGC) Program on the behavior of Micro, Small, and Medium Enterprises (MSMEs) in complying with Good Processed Food Manufacturing Practices (Cara Produksi Pangan Olahan yang Baik—CPPOB). This research employed a quantitative method with a descriptive approach. The respondents consisted of 80 processed food MSMEs participating in the PAGC Program in Medan City, Deli Serdang Regency, and Binjai City, selected using a purposive sampling technique. Primary data were collected through a Likert-scale questionnaire, while secondary data were obtained from documentation studies. Data were analyzed using descriptive analysis, validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing with IBM SPSS version 27. The results indicate that attitude, subjective norms, perceived behavioral control, and the role of PAGC facilitators have positive and significant effects, both partially and simultaneously, on MSME behavior in complying with CPPOB. The coefficient of determination (Adjusted R²) of 0.713 indicates that 71.3% of the variation in MSME compliance behavior with CPPOB is explained by these four variables, while the remaining 28.7% is influenced by other factors outside the research model. Among the independent variables, the role of PAGC facilitators was found to have the strongest influence on MSME compliance behavior. These findings suggest that strengthening positive attitudes, social support, perceived behavioral control, and effective facilitation through the PAGC Program can significantly improve MSMEs' compliance with CPPOB standards.